Pusat â Pinggiran Dunia Melayu di Nusantara: Dahulu dan Sekarang - Asnan, Gusti (SOSIOHUMANIKA, 2008)
ABSTRACT: âMelayu will never disappear from the earthâ is an expression that is often pronounced by the Malay people when they talk about the challenge faced by their culture and civilization. Their confidence, in some parts, seems true, because since the word of Malay for the first time was known (in the Chinese oldest sources ca. from the 7th century A.D.), it has survived until now. Not only that, in its long historical experiences, the term of âMelayuâ evolved perfectly, started from the name of a kingdom in Sumatra than became the name of race, culture and civilization which covered a huge region that is identical with Southeast Asia. The survival of the naming of Melayu, was not only supported by the relative intensive of research and publications that were carried out by the scholars, but also by the ability of the Malay people to defend their culture and civilization from continuous infiltration of other cultures and civilizations. It could be seen, for example, from the emergence of several centers of the Malayâs culture and civilization. The emergences of them have always been built through relationships with the peripheral areas. The center-periphery relationship could support the continuity of the Malay culture and civilization. The center could, in one time, decline and become peripheral area, and in the opposite the peripheral area could appear to the surface and become new center which dominates the social, political, economic and cultural life of the Malay world in general. This circle happened many times and colored the history of the Malay world. This article discusses the dynamic of several centers of the Malay culture and civilization in the longtime period and the center-periphery areas relationship. So that from this explanation could also be understood that it was a strategy of the Malay people to survive their culture and civilization in facing the strange culture and civilization.Key words: the Malay culture, dynamic of the center-periphery relationship, and strategy for preserving the Malay identity.About the Author: Dr. Gusti Asnan adalah Dosen di Jurusan Sejarah, Fakultas Sastra UNAND (Universitas Andalas) Padang, Sumatera Barat. Lahir di Lubuk Sikaping, Sumatera Barat, pada 12 Agustus 1962. Menyelesaikan pendidikan Sarjana (Drs.) di Jurusan Sejarah FS-UNAND Padang tahun 1986; dan menyelesaikan program Doktor (Dr.) di Fachbereich fuer Sozialwissenschaften Universitaet Bremen, Jerman tahun 1998 dengan menulis disertasi tentang Trading and Shipping Activities: The West Coast of Sumatra, 1819-1906. Beberapa buku dan artikelnya yang terbit pada beberapa waktu belakangan adalah Pemerintahan Daerah Sumatera Barat: Dari VOC Hingga Reformasi (2006), Kamus Sejarah Minangkabau (2003), dan âTransÂportation in the West Coast of Sumatra in the 19th Centuryâ dalam Bijdragen tot de Taal, Land en Volkenkunde (IV, 2002). Untuk keperluan akademis, penulis dapat dihubungi dengan alamat e-mail: gasnan@yahoo.comHow to cite this article? Asnan, Gusti. (2008). âPusat â Pinggiran Dunia Melayu di Nusantara: Dahulu dan Sekarangâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan,Vol.1, No.1 [Mei]. Bandung, Indonesia: Minda Masagi Press, UPI Bandung,Â  and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112, pp.13-26.Chronicle of the article: Accepted (January 15, 2008); Revised (March 11, 2008); and Published (May 20, 2008).